Assessment of the distribution and status of the Southern Pochard Netta e. erythrophthalma in South America - Freile, Juan F. (Wildfowl, 2016)
The Southern Pochard Netta erythrophthalma occurs in southern and eastern Africa, and in northern and eastern South America. It is widespread and common in Africa, where the population of the subspecies Netta e. brunnea is estimated at 30,000–70,000 individuals. Distribution of the nominate subspecies Netta e. erythrophthalma in South America is more localised, with breeding populations in the Caribbean and Pacific coasts, and the Andes from Venezuela south to the Andes in Argentina, and on the Atlantic coast of Brazil. Estimates of total numbers in South America, put at c. 25,000 birds, have been rather imprecise due to lack of data and likely overestimate the actual numbers. The species has been declining and contracting its range in South America since the 1970s. A review of the current distribution and status of Southern Pochard in South America suggests a major decline throughout most of its range, particularly in the Andes, Caribbean coast and Pacific lowlands, with no recent confirmed records from most of Colombia and Peru and dramatically reduced numbers in Ecuador. It is declining in Venezuela and numbers in Argentina have always been low. In Brazil the species is still numerous in Ceará south to Bahia and Goiás states, but apparently declining. Hunting and habitat loss from siltation, dredging and destruction of riparian vegetation appear to be the major threats. We estimate that the current maximum numbers are of 10,000 Southern Pochard in South America (although potentially as few as 5,000), making it necessary to update and revise the conservation status of this South American subspecies.